Design and simulation of MEMS saw resonator in CMOS technology - Noor Amalina Ramli (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
Modern consumers require wireless and mobile telecommunication device to be small, portable, high performance and have multitasking capabilities. Miniaturization of the widely popular surface acoustic wave (SAW) resonator on a silicon chip would be highly beneficial for integrated communication circuits. Conventionally, SAW device is implemented on the piezoelectric material which makes it incompatible with CMOS technology process. The latest advancement of micro electromechanical systems (MEMS) fabrication method allows miniaturization and integration of the SAW device with integrated circuits. This work presents the design and simulation of MEMS SAW resonator. There are two structures that have been developed; the first structure is a typical MEMS SAW resonator of 218MHz on LiNbO3 where the IDT and reflectors are deposited on top of the substrate. This structure was designed in order to study design parameters that affect the behaviour and performance of SAW resonator. The latter is a CMOS SAW resonator which comprises of four stacked layers: ZnO/Al/SiO2. Four resonators were modeled based on operating frequencies of 850MHz, 900MHz, 1.8GHz and 1.9GHz. The optimum thickness of ZnO is studied to improve the resonator performance. FEM simulation analysis using COMSOL MultiphysicsTM was conducted to obtain the resonance frequency that provides maximum displacement while Matlab was used to calculate the insertion loss. The finding shows that the resonator at 850MHz with 3.08μm thickness of ZnO is the most optimal design since it produces the lowest insertion loss 4.9dB and the highest Q factor 1411.